Pemetaan Ruang Terbuka Hijau Menggunakan Sistem Informasi Geografis dalam Pengendalian Penyakit Malaria : Literartur Review - Yoga Saputra; Inne Fadila; Poppy Serafani Harahap; Laura Tambunan; Elisa Sinaga (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
In Indonesia, approximately 70 million people live in malaria-endemic areas, putting them at risk of transmitting the disease to others. Geographic information systems (GIS) are essential tools for mapping and visualizing spatial characteristics, as well as analyzing detailed information. GIS first developed in the late 1950s and has been used in various industries, such as oil and gas, telecommunications, as well as agriculture, forestry, and green open spaces (RTH). This study employed a narrative literature review method, synthesizing previously published information on GIS in green open spaces. The results showed that the classification of aerial imagery using GIS can be divided into two main classes: 'private green spaces' and 'others'. This study focused on finding a significant amount of urban green space in informal settlements, which cover more than 10% of the area. The increase in the number of informal settlements is directly proportional to the increase in private green space. The study also noted that poor communities have access to urban green spaces, which can improve their quality of life. Identification and management of green spaces in informal settlements can strengthen residents' self-confidence and reduce the gap between formal and informal areas in cities.